Indirect treatment comparison of dabrafenib plus trametinib versus vemurafenib plus cobimetinib in previously untreated metastatic melanoma patients. Issue 1 (December 2017) - Daud, Adil; Gill, Japinder; Kamra, Sheily; Chen, Lei; Ahuja, Amit
Abstract Background Metastatic melanoma is an aggressive form of skin cancer with a high mortality rate and the fastest growing global incidence rate of all malignancies. The introduction of BRAF/MEK inhibitor combinations has yielded significant increases in PFS and OS for melanoma. However, at present, no direct comparisons between different BRAF/MEK combinations have been conducted. In light of this, an indirect treatment comparison was performed between two BRAF/MEK inhibitor combination therapies for metastatic melanoma, dabrafenib plus trametinib and vemurafenib plus cobimetinib, in order to understand the relative efficacy and toxicity profiles of these therapies. Methods A systematic literature search identified two randomized trials as suitable for indirect comparison: the coBRIM trial of vemurafenib plus cobimetinib versus vemurafenib and the COMBI-v trial of dabrafenib plus trametinib versus vemurafenib. The comparison followed the method of Bucher et al. and analyzed both efficacy (overall survival [OS], progression-free survival [PFS], and overall response rate [ORR]) and safety outcomes (adverse events [AEs]). Results The indirect comparison revealed similar efficacy outcomes between both therapies, with no statistically significant difference between therapies for OS (hazard ratio [HR] 0.94, 95% confidence interval [CI] 0.68 − 1.30), PFS (HR 1.05, 95% CI 0.79 − 1.40), or ORR (risk ratio [RR] 0.90, 95% CI 0.74 − 1.10). Dabrafenib plus trametinib differed significantly from vemurafenib plus cobimetinib with regard to the incidence of treatment-related AE (RR 0.92, 95% CI 0.87 − 0.97), any AE grade ≥3 (RR 0.71, 95% CI 0.60 − 0.85) or dose interruption/modification (RR 0.77, 95% CI 0.60 − 0.99). Several categories of AEs occurred significantly more frequently with vemurafenib plus cobimetinib, while some occurred significantly more frequently with dabrafenib plus trametinib. For severe AEs (grade 3 or above), four occurred significantly more frequently with vemurafenib plus cobimetinib and no severe AE occurred significantly more frequently with dabrafenib plus trametinib. Conclusions This indirect treatment comparison suggested that dabrafenib plus trametinib had comparable efficacy to vemurafenib plus cobimetinib but was associated with reduced adverse events.